2017
DOI: 10.1002/ps.4742
|View full text |Cite
|
Sign up to set email alerts
|

Resistance mechanism of Fusarium fujikuroi to phenamacril in the field

Abstract: In the field, the point mutation S219P or S219 L in Myosin-5 conferred high resistance to phenamacril in F. fujikuroi. The point mutation S219P did not affect the fitness of F. fujikuroi, while the point mutation S219 L decreased its fitness. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 24 publications
(54 reference statements)
3
67
0
Order By: Relevance
“…Phenamacril is a novel cyanoacrylate fungicide. It has an excellent antifungal effect on Fusarium species by inhibiting the ATPase activity of their myosin class I motor domains and has a good control effect on FHB . However, previous studies have shown that F. graminearum has a medium risk of resistance to this fungicide, which phenamacril cannot be used alone .…”
Section: Introductionmentioning
confidence: 99%
“…Phenamacril is a novel cyanoacrylate fungicide. It has an excellent antifungal effect on Fusarium species by inhibiting the ATPase activity of their myosin class I motor domains and has a good control effect on FHB . However, previous studies have shown that F. graminearum has a medium risk of resistance to this fungicide, which phenamacril cannot be used alone .…”
Section: Introductionmentioning
confidence: 99%
“…Benzimidazole fungicides bind to β‐tubulin to inhibit mycelial growth of plant pathogenic fungi, and the resistance mechanism is the point mutation of amino acids encoding the β‐tubulin in Botrytis cinerea and Sclerotinia sclerotiorum (Liu et al, , ; Zhu, Zhou, Li, Zhu, & Ma, ), or amino acids encoding the β 2 ‐tubulin gene in F. graminearum (Liu, Duan, Ge, Chen, & Zhou, ; Liu et al, ). The active target of the cyanoacrylate fungicide phenamacril is myosin 5 of the FGSC, and the point mutation in its coding gene leads to resistance of the FGSC to phenamacril (Hou et al, ; Li et al, ; Zheng et al, ). Therefore, there was no cross‐resistance between metconazole and carbendazim or phenamacril in F. graminearum , and positive cross‐resistance relationship between metconazole and epoxiconazole, difenoconazole or tebuconazole in F. graminearum .…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the prolonged use of only benzimidazole fungicides, carbendazim‐resistant isolates have developed in many plant pathogenic fungi, which leads to a decline in the efficacy of fungicides and the difficulty in controlling FHB (Liu, Che, & Chen, ; Liu et al, ; Qiu et al, , ; Yuan & Zhou, ). Although the cyanoacrylate fungicide phenamacril has high activity against the FGSC, previous studies have confirmed that it has a very high level of resistance risk for the FGSC and resistant isolates have been reported in F. fujikuroi , another member of the FGSC, in fields in China (Duan et al, ; Hou et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A novel cyanoacrylate fungicide called phenamacril (experimental code JS399‐19) was developed by the Jiangsu Branch of National Pesticide Research and Development Center of China in 1998 and showed specific antifungal activity towards Fusarium spp. Since 2007, it has been widely used in China for controlling FHB and rice bakanae disease caused by F. fujikuroi . Previous studies revealed that the class I myosin, FgMyoI is the drug target of phenamacril in F. graminearum .…”
Section: Introductionmentioning
confidence: 99%
“…Phenamacril directly binds with FgMyo1 and suppresses the ATPase activity of FgMyo1 . In the laboratory, substitution of an amino acid residue in FgMyo1 or its homologs in F. asiaticum and F. fujikuroi leads to high resistance to the fungicide . Until now, phenamacril resistant strains of F. graminearum have not been found in the field, while resistant strains of F. fujikuroi have existed in the field for some time .…”
Section: Introductionmentioning
confidence: 99%